Respiratory symptoms among domestic waste collectors Evsel atik toplayicilarinda solunum belirtileri - Loganathan Salvaraji; Mohammad Saffree Jeffree; Richard Avoi; Hazelina Mohd Akhir; Syed Sharizman Syed Abdul Rahim; Khamisah Awang Lukman (Logos Medical Publishing, 2020)
Objective: Increasing amount of waste concurrently increases the risk of exposure to hazardous materials among waste collectors. Vigorous exertion in the field intensifies the abundance of contaminated inspirable droplets. If left undetected and untreated, it may provoke significant pernicious health effects and redundant burdens to employees and employers. The purpose of this study is to determine the prevalence of respiratory symptoms and their associated factors among domestic waste collectors. Method: A cross-sectional study was conducted in Kota Kinabalu, Sabah between January and April 2020. Data were collected using a validated questionnaire which encompasses details about sociodemographic, health status, environment, and employment characteristics. Results: A total of 290 waste collectors with a mean age of 40 (±9) years old were participated in the study. Most of them were from Kadazan-Dusun-Murut ethnic origin with educational background till secondary school. The average monthly income of the workers was USD 298.45 (±171.9) per month, and they had been in service for 11 (±9.04) years. Respiratory symptoms were seen in 21% of the workers. The identified significant risk factors were determined as underlying chronic diseases (OR=2.34; 95% CI=1.054, 5.219) and contact with pets (OR=1.87; 95% CI=1.004, 3.288). Conclusion: Respiratory symptoms are prevalent amidst domestic waste collectors and related to their health and field activities.